Impact of Social Media on English Language Learning among Undergraduate EFL Learners: A Narrative Literature Review - Khurram, Shagufta; Palpandan, Sarala Thulasi (Development in Language Studies, 2023)
This review paper examines the existing literature on the impact of social media on English language learning for undergraduate EFL learners. The primary objective of the study was to investigate the impact of social media on the acquisition of English language skills by EFL learners. A narrative review was done, analyzing data from two online databases, namely Google Scholar and Science Direct, covering the period from 2018 to 2022. The findings indicate that various social media applications have a positive influence on EFL students' ability to learn English as a foreign language. However, a few research studies also uncovered a detrimental effect of social media on young learners worldwide, particularly in Pakistan, concerning English language learning. This study work intends to investigate and synthesize existing studies, theories, and findings in this field by conducting a narrative literature review on the impact of social media on English language learning among university EFL learners. It will advance knowledge of the possible advantages and difficulties of incorporating social media into language learning environments and offer guidance to educators, researchers, and policymakers on how to improve English language instruction for undergraduate EFL students. Based on this comprehensive review of the available literature, it is recommended that further research be conducted to focus on the negative impact of social media on English language learning, particularly in Pakistan where limited research has been done in this area. Additionally, it is suggested that future research in this field adopts a mixed-method research design, as there is a research gap in terms of methodology in the existing literature review.